Analisis Pengendalian Kualitas Produk X Dengan Metode Six Sigma (DMAIC) Pada PT. XYZ - Hafizh Hakim Hidajat; Ade Momon Subagyo (Peneliti.net, 2022)
This research was conducted to determine the level of process capability in the production process of defective products in product X. The method used is the Six Sigma approach with the DMAIC concept (Define, Measure, Analyze, Improve and Control). The tools used are CTQ, SIPOC Diagram, Pareto Diagram, Fishbone Diagram and Five M Checklist. From the results of data processing, the DPMO value is 439.83 which means that in one million opportunities there are 439.83 possibilities of the resulting product will experience defects. Product X has a sigma level of 4.8 with the largest percentage of defects found in the Weld Line (39.7%), NG Initial Setting (27.56) and Short Mold (13.82%). After analyzing, it can be concluded that the causes of disability are human factors, methods, machines and materials. Then suggestions for improvement from the causes that have been determined on the Fishbone diagram are given using the Five M Checklist tools. And finally, the Control stage is carried out which focuses on documenting and disseminating information on the corrective actions that have been proposed previously.